2012
DOI: 10.1186/1471-2474-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vertebral fractures in women and men in the population-based Tromsø Study

Abstract: BackgroundOsteoporotic vertebral fractures are, as the hip fractures, associated with increased morbidity and mortality. Norway has one of the highest reported incidences of hip fractures in the world. Because of methodological challenges, vertebral fractures are not extensively studied. The aim of this population based study was to describe, for the first time, the age- and sex specific occurrence of osteoporotic vertebral fractures in Norway.MethodsData was collected in the Tromso Study, 2007/8 survey. By th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
6
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 47 publications
12
78
6
4
Order By: Relevance
“…The European Vertebral Osteoporosis Study suggests that 12% of men and women aged 50-80 years have a radiographic vertebral fracture, with higher prevalence found in higher ages [7]. Other reports support an increasing prevalence by aging in both genders [8][9][10]. However, although the prevalence seems to be higher in young adult men than in young adult women [11], incident fractures are more common in old women than in old men [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The European Vertebral Osteoporosis Study suggests that 12% of men and women aged 50-80 years have a radiographic vertebral fracture, with higher prevalence found in higher ages [7]. Other reports support an increasing prevalence by aging in both genders [8][9][10]. However, although the prevalence seems to be higher in young adult men than in young adult women [11], incident fractures are more common in old women than in old men [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the different methods used to assess the presence of radiological vertebral deformities in other studies should be carefully considered, the present results suggest that the prevalence of VFs in this particular clinical setting is probably more elevated than that observed in healthy Caucasian population, which, in large epidemiologic studies [2,3], was estimated to be between 10 and 20% in people aged over 60.…”
Section: Discussionmentioning
confidence: 61%
“…Large epidemiological studies have been carried out in the general population, and have shown that the prevalence of VFs is high, and increases with age in both sexes [2,3]. Moreover, it has been demonstrated that VFs represent a relevant risk factor for death [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, some limitations include the requirement for highly experienced readers and modest reproducibility between readers, particularly for mild vertebral fractures (7,23). Indeed, the fracture prevalence in the EVOS study dropped to 12.0% after using the McCloskey predictors of fracture risk (2,33). Although the retrospective nature of study prevented the documentation of all possible effectual factors on fracture risk, we found that patients with fractures were slightly older, thinner, and taller than those with no fracture.…”
Section: Distribution Of Prevalent Fracturesmentioning
confidence: 85%